Perimbangan Gypsum Bonded Investment terhadap Penysutan Logam Paduan Emas pada Saat Pengecoran - Ronnie Rusli (Faculty of Dentistry, Universitas Indonesia, 2015)
Gypsum bonded investment is usually used for dental gold alloys casting procedure. Casting alloys shrink during solidified from melting temperature to room temperature. In order to obtain an accurate restoration, the shrinkage of the alloy should be compensated by the expansion of the investment at the time of casting procedure. Ideally, the shrinkage of the alloy is equal to the expansion of the investment. However, no investment material fulfills this ideal condition properly. In this paper, how the investment material compensated the shrinkage of the casting alloys will be described briefly.